The royal letters of Baginda Omar : Sultan Terengganu Darul Iman IX Marhum Baginda (1806-1876) volume I - Raimy Che-Ross; Yayasan Diraja Sultan Mizan (Kuala Terengganu : Yayasan DiRaja Sultan Mizan, 2015)
Sultan Terengganu Darul Iman IX, Marhum Baginda (1806-1876).
volume 1. The royal letters of Baginda Omar : Sultan Terengganu Darul Iman IX Marhum Baginda (1806-1876).
Includes index and bibliography : pages 315-329.
Keywords: Terengganu (Sultanate) -- History; Terengganu (Sultanate) -- Kings and rulers